Pembelajaran Kitab Mubadi’ Fiqih sebagai Upaya Penguatan Pemahaman Fiqih dan Mufrodat Bahasa Arab Santri di Ma’had Walisongo 1 Maron, Probolinggo - Dian Zahrotus Sita; Ainur Rofiq Sofa (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
The study of classical Islamic texts (kitab kuning) in Islamic boarding schools (pesantren) plays a crucial role in strengthening students’ religious understanding as well as enhancing their mastery of the Arabic language. One of the foundational texts taught is Mubadi’ Fiqih, which contains basic principles of Islamic jurisprudence and serves as an introductory bridge for students to comprehend Arabic religious texts. This research aims to analyze the implementation of Mubadi’ Fiqih learning as an effort to strengthen students’ understanding of fiqh and enrich their Arabic vocabulary (mufrodat) at Ma’had Walisongo 1 Maron, Probolinggo. The study employs a qualitative approach with a case study design. Data were collected through classroom observations, in-depth interviews with the headmaster, teachers, and students, as well as documentation of the learning process. The findings reveal that the learning process applies bandongan and sorogan methods, supported by vocabulary translation exercises and contextual explanations of fiqh terminology. These strategies effectively enhance students’ comprehension of basic Islamic legal concepts while simultaneously expanding their Arabic vocabulary in religious contexts. Moreover, the teachers’ consistency in explaining Arabic sentence structures and assigning vocabulary memorization tasks significantly supports the learning outcomes. However, challenges such as students’ varying initial language proficiency and limited class time remain obstacles to achieving optimal results. Overall, the Mubadi’ Fiqih learning approach proves to be an effective integrative medium for strengthening both fiqh knowledge and Arabic linguistic competence among pesantren students.